Prurigo Nodularis after Radiotherapy: An Isoradiotopic Response? - Caspar Weel Krammer; Rami Mossad Ibrahim (Case Reports in Dermatological Medicine)
Prurigo nodularis is a rare and chronic skin disorder with multiple, pruritic, and firm nodules. The exact pathophysiology is still unknown. Skin disorders appearing at sites of radiation can be defined as isoradiotopic. A 35-year-old male had developed a skin lesion in the left submandibular area on a base of irradiated skin which was initially suspected as a skin malignancy. The patient had a history of undifferentiated nasopharyngeal cancer with lymph node involvement which was treated by radiochemotherapy thirteen years previously. Histological examination confirmed that it was a case of prurigo nodularis which subsequently evolved at distant sites. This presentation may suggest a case of an isoradiotopic response.